1261. Antimicrobial Susceptibilities of Carbapenem-Resistant Klebsiella pneumoniae (CRKP) Isolates from a Multi-state Network of Long-term Acute Care Hospitals (LTACHs). (4th December 2021) - Zhang, Helen L; Han, Jennifer; Alby, Kevin; Lapp, Zena; Snitkin, Evan; Goldstein, Ellie J C; Muldoon, Sean R; Tolomeo, Pam C; Lautenbach, Ebbing
Abstract: Background: CRKP infection is common among LTACH patients. However, CRKP antimicrobial susceptibility testing (AST) with newer antibiotics has not been described in this population. In this study, we performed AST on CRKP in LTACHs. Methods: CRKP clinical cultures were collected from 21 Kindred Healthcare LTACHs (12 southern California, 6 Texas, 2 Florida, 1 Kentucky) from 8/1/14-7/25/15. AST was performed using a custom Sensititre TM broth microdilution panel (ThermoFisher Scientific, Waltham, MA). 2021 Clinical & Laboratory Standards Institute interpretive criteria were used for all agents except plazomicin (PLZ), for which US Food and Drug Administration breakpoints were used. Results: 459 CRKP clinical isolates were collected, including 254 (55.5%) respiratory, 155 (33.8%) urine, 39 (8.5%) blood, and 10 (2.2%) wound cultures. Most (419, 91.0%) were from southern California. 151 (32.9%) were colistin-resistant. 42 (9.2%) isolates were non-susceptible to meropenem-vaborbactam (MVB), 16 (8.9%) to imipenem-relebactam (IPR), 4 (0.9%) to ceftazidime-avibactam (CZA), and 3 (0.7%) to PLZ. Cross-resistance patterns are shown in Table 1. Among southern California facilities, there was significant inter-facility variation in MVB non-susceptibility (Pearson's chi-squared test, p=0.005) but not in CZA, IPR, or PLZ non-susceptibility. Table 1. Cross-resistance to antimicrobials among carbapenem-resistant Klebsiella pneumoniae isolates from 21 Kindred long-term acute care facilities, August 1, 2014 – July 25, 2015 (N=459). Number of isolates and column percentages reported. 2021 Clinical & Laboratory Standards Institute interpretive criteria are used for all agents except for PLZ, for which US Food and Drug Administration breakpoints are used. Abbreviations: CST = colistin. CZA = ceftazidime-avibactam. I = intermediate. IPR = imipenem-relebactam. MIC = minimum inhibitory concentration. MVB = meropenem-vaborbactam. PLZ = plazomicin. R = resistant. S = susceptible. Conclusion: In this sample of CRKP isolates from LTACHs in 2014-2015, nearly 10% of isolates were non-susceptible to MVB or IPR, respectively, despite neither agent being commercially available at the time. In contrast, there was a low prevalence of non-susceptibility to CZA, which received initial US Food and Drug Association approval in 2/2015, and PLZ, which was not commercially available during the study period. Cross-resistance between CZA and carbapenem/beta-lactamase combination antibiotics was uncommon. Future studies should evaluate CRKP susceptibilities to new agents in post-marketing cohorts and identify risk factors for resistance. Disclosures: Jennifer Han, MD, MSCE, GlaxoSmithKline (Employee, Shareholder) Ebbing Lautenbach, MD, MPH, MSCE, Merck (Other Financial or Material Support, Member of Data and Safety Monitoring Board (DSMB))